Chemical and Structural Changes of Ozonated Empty Fruit Bunch (EFB) in a Ribbon-Mixer Reactor - Amnani Shamjuddin; Nor Aishah Saidina Amin; Nurul Suhada Abdur Rasid (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Agricultural wastes especially empty fruit bunch (EFB) are abundantly available to be utilized as a feedstock for biochemical synthesis or biofuel production. The components of the waste include lignin, hemicellulose and cellulose. Cellulose, the polymer of glucose, is the active component for producing bio-based chemicals. However, it is difficult to isolate cellulose since lignin, the most outer layer in the waste is recalcitrant. Therefore, the agricultural wastes need to be pre-treated prior to downstream processing. The aim of this study was to investigate the effect of ozone pretreatment on lignin degradation and total reducing sugar (TRS) yield. EFB was pre-treated using ozone gas in a ribbon-mixer reactor. The chemical and structural changes of ozonated EFB were analysed. The highest delignification obtained were 95.7 wt.% and TRS yield was enhanced to 84.9% at a moisture content of 40 wt.% with 60 g/m3 ozone concentration within one hour of reaction time. Both NMR and FTIR spectra conferred major peaks inferring higher lignin degradation could be achieved using ozonolysis. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).